Enzymatic treatment of deinking sludge – effect on fibre and drainage properties. Issue 21 (2nd November 2018) - Steffen, Friedrich; Janzon, Ron; Saake, Bodo
ABSTRACT: This work focused on the enzymatic treatment of deinking sludge (DS), a waste stream arising from German deinked pulp mills. Three industrial DS samples were characterised with respect to chemical composition and fibre morphology. In this study, four cellulase enzyme preparations were tested under neutral pH conditions and one cellulase was identified as suitable for DS conditioning with no need of pH adjustment. Additionally, our approach shows that inorganic particles contained in the DS samples do not negatively affect cellulase activity, as illustrated by respectable hydrolysis yields of up to 61%. Enzymatic treatment of DS led to fibre shortening and fibre fines generation with increasing enzyme dose and incubation time. The dewaterability of enzyme-treated DS samples was tested and the results showed that high amounts of fibre fines enhanced filter cake consolidation during dewatering, resulting in higher cake solids. A 10–14 percentage point increase in cake solids was obtained depending upon the enzyme dose applied, the origin of the DS sample, and the exposure period. Through the enzymatic treatment the annually generated amount of DS in Germany could be reduced by up to 20%, which would mean considerable disposal cost savings.